Analisis Faktor Penyebab Kelambatan Penyaluran Dana Desa: Studi Kasus di Kecamatan Membalong Kabupaten Belitung - Sri Suryanovi (Jurnal Kewidyaiswaraan, 2019)
The realization of Village Fund distribution from the State Treasury Account to the Regional Public Account (RKUD) and from the RKUD to the Village Cash Account in 2017 and 2018, generally is slowness, so the realization of Village Fund absorption and output achievements not on targeted. This study aims to knowing causative factors the slowness, especially in the villages in Kecamatan Membalong Kabupaten Belitung, so that it is entitled "Analysis of Factor Causing Slowness in Village Fund Distribution: A Case Study in Kecamatan Membalong Kabupaten Belitung." This study is qualitative explorative. From the study it was concluded that the slowness in distribution Village Funds over there occurs because the slow submission of Village Fund distribution requirements documents from the village head to bupati, so that the submission of Village Fund distribution requirements documents from bupati to the head of the State Treasury Office was late. The root of the problem is first, the communication factor. Second, attitude factors. Third, a resource factor. Fourth, a bureaucratic factors. Fifth, regulatory factors. Than, the six other factors, namely the difficulty of geography, demography, and public facilities owned by the Village.